Characterisation of the membrane-extrinsic domain of the TatB component of the twin arginine protein translocase. - Maldonado, B; Kneuper, H; Buchanan, G; Hatzixanthis, K; Sargent, F; Berks, B; Palmer, T (2011)
The twin arginine protein transport (Tat) system transports folded proteins across cytoplasmic membranes of bacteria and thylakoid membranes of plants, and in Escherichia coli it comprises TatA, TatB and TatC components. In this study we show that the membrane extrinsic domain of TatB forms parallel contacts with at least one other TatB protein. Truncation of the C-terminal two thirds of TatB still allows complex formation with TatC, although protein transport is severely compromised. We were unable to isolate transport-inactive single codon substitution mutations in tatB suggesting that the precise amino acid sequence of TatB is not critical to its function.